Die Welterfahrung des Autodidakten: fremde Länder und Sprachen in den Büchern Leonhard Thurneyssers zum Thurn = Experiencing the world as a self-taught man - Bulang, Tobias (Daphnis, 2017)
Leonhard Thurneysser zum Thurn (1531-1596), personal physician of Brandenburg’s elector, was an alchemist, astrologist, pharmacist, entrepreneur, and printer of a large number of books, which he himself wrote. In these publications, he repeatedly refers to experiences he gained by traveling the world. His books also included many foreign alphabets and languages (via remarkable typography), thus insinuating an overall language proficiency. This study examines how Thurneysser used travel and languages for self-fashioning.